Adjusted MVA : enhancing the fundamental approach to higher share returns. - Loh, Emily Wei Xian. (2008)
The aim of this paper is to find out if the Adjusted MVA enhances a traditional set of fundamental ratios in indicating superior stock returns in a portfolio investment. The findings conclude that the Adjusted MVA does significantly enhance its traditional counterparts in indicating superior stock returns.